The anatomy of neoliberalism and education : imperialism, class struggle, and pedagogy - Nikolakaki, Maria, 1962- (Marxist, socialist, and communist studies in education, 2022)
"This book is about the Anatomy of Neoliberalism and Education from a Marxist perspective. It is the dialectical materialism of neoliberal ideas, examining the material conditions of how these ideas and practices emerged, and under what conditions. Each of these elements is related to the other and can only be properly understood as part and parcel of the whole system of capitalism, which links them together. This book investigates neoliberalism's political, cultural, and financial tools. It goes deep in the forces who have supported neoliberalism and how it became "common sense". It explores the imperialist outcomes and the social devastation it created. It then goes to see how these ideas and policies have been implemented in education. In short, it is the materialist conception of the history of the American empire. It then uses the analytic tools developed through this investigation to re-read the neoliberal educational reforms"--